Hubungan Hygiene Perorangan dan Pemakaian Alat Pelindung Diri (APD) dengan Keluhan Gangguan Kulit dan Kecacingan pada Petugas Pengangkut Sampah Kota Pematangsiantar Tahun 2012 - Marlina Renta Juyanti Butarbutar; taufik ashar; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
Waste is something material or solid objects that are no longer used by humans and discarded. Worse system of waste management can be a negative impact on health. In addition to infecting the skin, the disease can be congenital garbage worm infections. One of the people at risk for skin disorders and intestinal worms are officers garbage. It is necessary to know the relationship between personal hygiene and using of personal protective equipment (PPE) with complaints of skin disorders and worm on Pematangsiantar waste transporter officer. The purpose of this study was to determine the relationship of personal hygiene and using of personal protective equipment (PPE) with complaints of skin disorders and worm on Pematangsiantar waste transporter officer in 2012. This research is analytic survey research to a sample of 45 respondents were selected by simple random sampling method. The method used was interviews using questionnaires and took examinations on faecal worm respondent. The results showed that all respondents have good personal hygiene in the category so that data analysis can not be done. Fisher's exact test results, there was no significant relationship between the use of personal protective equipment with complaints of skin disorders (p = 0.321) and worms (p = 0.613). The Sanitation Department is expected in order to further improve sanitation and provide personal protective equipment for transporter officer. Also expected to cooperate with the Health Department in an effort to educate officers about personal hygiene and the using of personal protective equipment at work so they do not pay attention to personal hygiene and disease associated with waste.   Key Words: Personal Hygiene, Personal Protective Equipment, Complaint of Skin Disorders, Worms